Investment deregulation and innovation performance of Chinese private firms - Zhang, Jianhong; Jiang, Jiangang (Journal of Financial Stability, 2024)
This study explores the effect of an investment system reform (deregulation) on the innovation performance of private firms in China. Using a difference-in-differences approach on the data on patent applications of private firms from 1998 to 2009, this study confirms the positive relationship between investment deregulation and innovation performance. We also find that the positive relationship is moderated by types of innovation, firm size and international orientation, and regional patent promotion policy. The study further finds evidence that investment deregulation stimulates innovation performance through two mechanisms, the escaping competition effect, and the preemptive patenting effect. Moreover, investment deregulation may improve the innovation performance of private firms by encouraging investment in fixed capital.